Courses
Courses for Kids
Free study material
Offline Centres
More
Store

# Prove that $\operatorname{cosec} \theta \sqrt {1 - {{\cos }^2}\theta } = 1$

Last updated date: 02nd Aug 2024
Total views: 418.5k
Views today: 12.18k
Verified
418.5k+ views
Hint: In this question, we will proceed by considering the L.H.S part of the given equation. Then use the formula in trigonometric identities and trigonometric ratios to prove that the L.H.S part of the given equation is equal to the R.H.S part.

Given equation is $\operatorname{cosec} \theta \sqrt {1 - {{\cos }^2}\theta } = 1$
We know that $1 - {\cos ^2}\theta = {\sin ^2}\theta$. By using this formula, we have
$\Rightarrow {\text{L}}{\text{.H}}{\text{.S}} = \operatorname{cosec} \theta \sqrt {{{\sin }^2}\theta } \\ \Rightarrow {\text{L}}{\text{.H}}{\text{.S}} = \operatorname{cosec} \theta \left( {\sin \theta } \right) \\$
We know that $\operatorname{cosec} \theta = \dfrac{1}{{\sin \theta }}$. By using this formula, we have
$\Rightarrow {\text{L}}{\text{.H}}{\text{.S}} = \operatorname{cosec} \theta \sqrt {{{\sin }^2}\theta } \\ \Rightarrow {\text{L}}{\text{.H}}{\text{.S}} = \dfrac{1}{{\sin \theta }}\left( {\sin \theta } \right) = \dfrac{{\sin \theta }}{{\sin \theta }} \\ \Rightarrow {\text{L}}{\text{.H}}{\text{.S}} = 1 \\ \therefore {\text{L}}{\text{.H}}{\text{.S}} = {\text{R}}{\text{.H}}{\text{.S}} \\$
Hence, proved that $\operatorname{cosec} \theta \sqrt {1 - {{\cos }^2}\theta } = 1$.
Note: Here we have used the trigonometry identity ${\sin ^2}\theta + {\cos ^2}\theta = 1 \Rightarrow 1 - {\cos ^2}\theta = {\sin ^2}\theta$ and the trigonometric ratio $\operatorname{cosec} \theta = \dfrac{1}{{\sin \theta }}$. So, in solving these types of questions, remember all the formula n trigonometry to solve easily.